درجة جاذبية مركز التسوق و علاقتها بعوامل استكشاف المسار - جمال الأحمر; لين ونوس (Tishreen University, 2019)
In the context of monitoring and understanding the relation between the shopping malls attractiveness and wayfinding factors. The research aims to provide a range of important indicators for designers and developers during the program and design stages to ensure satisfaction of potential shoppers, through a practical approach that has demonstrated a strong and positive relationship between shopping malls attractiveness and wayfinding, emphasizing the importance of architectural design and interior design as an important wayfinding factor and effective attraction tool.   في إطار رصد وفهم العلاقة بين جاذبية مركز التسوق وعوامل استكشاف المسار. يهدف البحث إلى تقديم مجموعة من المؤشرات هامة للمصممين والمطورين خلال مرحلتي وضع البرنامج والتصميم لضمان تحقيق رضا المتسوقين المحتملين، وذلك من خلال منهج تطبيقي ساعد في اثبات وجود علاقة قوية طردية بين جاذبية مركز التسوق واستكشاف المسار، والتأكيد على أهمية التصميم المعماري والتصميم الداخلي كعامل استكشاف مسار مهم وأداة جذب فعالة.